Cover Picture: A Remarkable Catalyst Combination to Widen the Operating Temperature Window of the Selective Catalytic Reduction of NO by NH3 (ChemCatChem 8/2014). Issue 8 (August 2014) - Zhang, Runduo; Liu, Ning; Luo, Zhen; Yang, Wei; Liang, Xin; Xu, Ruinian; Chen, Biaohua; Duprez, Daniel; Royer, Sébastien
<x xml:space="preserve">Abstract</x> Cover all your bases The cover image shows the principle of catalyst combination for an ideal autoexhaust control that covers a broad temperature range. In their Full Paper on p. 2263 ff., R. Zhang, S. Royer and co‐workers describe a remarkable catalyst combination, of MnCeTi and VWTi active materials, that operates over a broad operating temperature window (from 150 to 400 °C). Fundamental evidence is given for the rational design of the process and its efficiency maximization resulting in an excellent selective catalytic reduction performance.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>